Preparation of Sulfonylcalix[4]arene-loaded XAD-7 Resin for Strontium(II) Adsorption. Issue 3 (May 2019) - Liu, Cong; Su, Guofeng; Chen, Tao; Liang, Manchun; Zhao, Liting; Zhang, Dongxiang
Abstract: Sulfonylcalix[4]arene-loaded XAD-7 Resin was prepared and used as an adsorbent for removal of Strontium(II) from aqueous solutions. The adsorption of the metal ions onto SCA-XAD-7 as a function of pH, contact time, metal ions concentration, temperature, and reuses was investigated. The adsorption capacity of SCA-XAD-7 composite towards tested ions reached a maximum at pH values of ∼6. The adsorption has reached equilibrium within 7 h. The adsorption isotherms were well fitted by the Langmuir model, and the maximum values of adsorption capacity of the adsorbent were 28.87 mg⋅g −1 . Thermodynamic studies imply the adsorption was a spontaneous and exothermic process in nature.